(untitled) (Research, Society and Development, 2022)
HMG-CoA reductase (3-hydroxy-3-methylglutaryl-coenzyme A reductase) is the enzyme that plays a limiting role in cholesterol biosynthesis. Among the HMG-CoA reductase inhibitor molecules, statins stand out, a class of drug used in the treatment of atherosclerosis and in the reduction of high cholesterol levels, therefore they are biomolecules of medical and pharmaceutical importance. In this context, this work aimed to carry out a systematic mapping of patents and scientific articles related to the biosynthesis of HMG-CoA reductase inhibitors. The search was carried out in the databases of the National Institute of Intellectual Property (INPI), the European Patent Office (Espacenet), the Derwent Innovations Index, the World Intellectual Property Organization (WIPO) and also articles indexed in Scielo and Pubmed using as descriptors “statins”, “production and statins and fungi”, “statins and fungus”. Of the 2561 cataloged patents, 09 were included because they met the inclusion criteria. The number of scientific articles found in the databases was higher (2820) when compared to the number of patents. As a country, China represents the largest holder on the subject, corresponding to 88.9% of patented products. Based on the mapping, advances in the search for strategies for the biotechnological production of statins can be highlighted. Some of the inventions used microorganisms such as filamentous fungi associated with agro-industrial substrates as an alternative and low-cost source for the production of statins to replace synthetic sources. However, future studies can be carried out using new fungi and new renewable substrates, considering the existing biodiversity worldwide.